Toxicidad aguda y dosis letal del hexafluorosilicato de magnesio en ratas - Sotomayor Camayo, Justiniano (2001)
We've inade an experimental investigation to evaluate the toxicity of hexafluorosilicato of magnesium above the behaviour clinical and the hepatic and gastric tissues reactionsftont anunals of experimentation. We selection 40 male of albicans rats "spraguie dowley" of 250 gr of weight procedents of similars boxes and we sellectionated seven experimental groups about the next dosis of hexafluorosilicato demostrated in water that we used. Group A 2.5 mg., group B 5 mg., group C 10 mg., group D 15 mg., group E 20 mg., group F 25 mg., group G 30 mg. A group of five, it was considerated control that we agregated pure water. The clinical action was evaluated insix hours through the clinical characteristicssince unquiet to death. Rats were sacrificated then of six hours ofthe administration of the dosis and we proceded in the cut histologic preparation of hepatic and gastric tissues. The results indicate that dosis of 20 ing. thesymptorns more frecuency was the depression (60%), With 25 ing. it deniostrated depression (100%) in the first tinze; chirrido (60%) in the third tinie; death (60%) in thesixth time; voinit (40%) in the third little, and diarrea (20%) in thefifth hour With 30 ing. we./ound depression (100%) in thefirst tilue; chirrido (80%) in the second little; death (60%) in the fourth time, and voinit (40%) in the third hour. With the test of chi-cuadrado we foundsignificant di/Prences beoven the dosis and the critical ofthe symptonis evaluated P<0.001 the histologics obvervalion,s indicate norinal caracterislics in less dosis of 20mg. With 20 mg we observated 28% vascular congestion and 72% of normaly 25 mg. we noticed 76% of vascular congestion and 24% of leucocitarv infiltrated with 30 mg. We noticed 52% ofleucocitary intiltrated and 48% vascular congestion. We found differents beoven the increment of the dosis and the histologies modifications obvservated in the studY of the animal (p<0.001).